A Nickel(II) Nitrite Based Molecular Perovskite Ferroelectric. Issue 26 (24th May 2019) - Xiong, Yu‐An; Sha, Tai‐Ting; Pan, Qiang; Song, Xian‐Jiang; Miao, Shu‐Rong; Jing, Zheng‐Yin; Feng, Zi‐Jie; You, Yu‐Meng; Xiong, Ren‐Gen
Abstract: The X‐site ion in organic–inorganic hybrid ABX3 perovskites (OHPs) varies from halide ion to bridging linkers like HCOO −, N3 −, NO2 −, and CN − . However, no nitrite‐based OHP ferroelectrics have been reported so far. Now, based on non‐ferroelectric [(CH3 )4 N][Ni(NO2 )3 ], through the combined methodologies of quasi‐spherical shape, hydrogen bonding functionality, and H/F substitution, we have successfully synthesized an OHP ferroelectric, [FMeTP][Ni(NO2 )3 ] (FMeTP =N ‐fluoromethyl tropine). As an unprecedented nitrite‐based OHP ferroelectric, the well‐designed [FMeTP][Ni(NO2 )3 ] undergoes the ferroelectric phase transition at 400 K with an Aizu notation of 6/ mmm F m, showing multiaxial ferroelectric characteristics. This work is a great step towards not only enriching the molecular ferroelectric families but also accelerating the potential practical applications. Abstract : Through a combination of quasi‐spherical shape, hydrogen bonding functionality, and H/F substitution, a molecular perovskite ferroelectric was successfully synthesized, [FMeTP][Ni(NO2 )3 ] (FMeTP =N ‐fluoromethyl tropine). As an unprecedented nitrite‐based molecular ferroelectric, it undergoes a ferroelectric phase transition at 400 K with an Aizu notation of 6/ mmm F m, showing multiaxial characteristics.